7-3x=5-6x

Simple and best practice solution for 7-3x=5-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-3x=5-6x equation:



7-3x=5-6x
We move all terms to the left:
7-3x-(5-6x)=0
We add all the numbers together, and all the variables
-3x-(-6x+5)+7=0
We get rid of parentheses
-3x+6x-5+7=0
We add all the numbers together, and all the variables
3x+2=0
We move all terms containing x to the left, all other terms to the right
3x=-2
x=-2/3
x=-2/3

See similar equations:

| 35=v/3+15 | | -4(20-2x)=12(x-6.5) | | 0.3x+2=0.4x-0.5 | | -5(3x+4)=-170 | | w/4+11=17 | | -2x+-4=2x+12 | | 3x+9-2x=-12-5x | | ​3(4x-2)-5x=6-7(-x-2) | | 2.61x+81=6.8121+9x | | 8(x+5)=x+21 | | 16x=16x+8 | | 7(x+5)=x+21 | | 2/3c-14=-20 | | 6(x+5)=x+21 | | 2x+4x+40-x=50 | | Y-x2-5=0 | | x-52=2x | | 50+3x=20+5x | | 8−3w=5 | | 2x+2=6x-15 | | (x-2)=1/4(8x-12) | | 1x-6=-4x+18 | | 4=3a+13 | | 6•12x= | | 100-4x=74-6x | | (x-2)+(x-2)+(x)+(x+2)+(x+2)-4=10 | | 4(x-3)=2x+30 | | 180=11x+14 | | 100-5x=74-6x | | 3(1-6x)=57 | | 6=u. | | 94-4x=74-6 |

Equations solver categories